MicroRNA‐21 promotes osteogenic differentiation of mesenchymal stem cells by the PI3K/β‐catenin pathway. Issue 7 (21st May 2015) - Meng, Yu‐Bin; Li, Xue; Li, Zhao‐Yang; Zhao, Jin; Yuan, Xu‐Bo; Ren, Yu; Cui, Zhen‐Duo; Liu, Yun‐De; Yang, Xian‐Jin
ABSTRACT Osteogenesis of mesenchymal stem cells (MSCs) is essential for bone repair. Recently, microRNAs have been proven to play an important role in the regulation of MSC differentiation, including osteogenesis. Here, the function of microRNA‐21 (miR‐21) in the osteogenic differentiation of human umbilical cord mesenchymal stem cells (hUMSCs) was investigated. Briefly, the miR‐21 mimics (m‐miR‐21) and the antisense miR‐21 (as‐miR‐21) were transfected to hUMSCs, and the capacity of miR‐21 for the osteogenic differentiation of hUMSCs was evaluated by the expression of osteogenic markers encoding alkaline phosphatase (ALP), runt‐related gene‐2 (RUNX‐2) and osteocalcin (OCN), as well as by Alizarin red S staining. The results indicated that the overexpression of miR‐21 elevated the expression level of the osteogenesis‐related genes of hUMSCs. During this process, the PI3K‐AKT signaling pathway activity had an increasing tendency responding to miR‐21 up‐regulation. This enhancement promoted the phosphorylation of GSK‐3β, leading to the stabilization and high concentration accumulation of β‐catenin in cytoplasm to activate the transcription of RUNX‐2, and finally increased the osteogenesis of hUMSCs. This work demonstrated that miR‐21 and its target PI3K‐AKT‐GSK3β pathway played an important role in the osteogenic differentiation of hUMSCs by stabilizing β‐catenin. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:957–964, 2015.